Exploration of Dakwah Bilhaal and Billisaan in the Digital Era An Islamic Communication Perspective - Hidayat, Yogi Fery (Civiliza Publishing, 2025)
This study examines the transformation of the dakwah methods of bilhaal (role modeling) and billisaan (verbal communication) in the digital era from the perspective of Islamic communication. The study employs a qualitative approach based on literature review, analyzing the role of digital media in supporting dakwah in accordance with the principles of Islamic communication. The findings of this research include the fact that bilhaal, which emphasizes real-life behavior, has now shifted to social media, presenting challenges to authenticity in the digital world. Meanwhile, billisaan utilizes various digital platforms such as YouTube, podcasts, and Instagram Live, providing opportunities to reach a global audience interactively. Digital media expands the reach of dakwah, enhances interactivity, and offers flexible formats. However, challenges such as the risk of excessive image-building, information distractions, and superficial understanding also arise. This study also finds that relevant, inspiring, and contextual digital dakwah can meet the spiritual needs of an increasingly complex society, especially the younger generation. With an approach that integrates both traditional and digital methods, dakwah can become an effective instrument for social and spiritual transformation.